(untitled) (Journal of Asian Development Studies, 2015)
Education plays an elementary role in human capital formation and economic development of an economy. Mincerian earning function was estimated for the Punjab province and a comparative analysis was made between financial and agriculture sectors. The results showed that 8.4 percent increase in earnings per month was observed due to an additional year of education in financial sector whereas 7.5 percent increase in earnings per month was observed due to an additional year of education in agriculture sector. The results also showed that, returns to experience were higher in agriculture sector as compared to financial sector. The females earned approximately two times less than their male counterparts in financial sector. Male of agriculture sector earned three times more than their female counterparts. A remarkable positive impact of education and experience was observed on earnings in both sectors of the Punjab. The analysis showed that people engaged in financial sector earned higher wages as compared to agriculture sector